(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify the bacterial etiology, antibiotic resistance status of typical bacteria isolated from urine samples, and some related factors. Subjects and methods: Patients with urinary tract infections who underwent urine culture and antibiotic susceptibility testing, with clear information, and who were hospitalized at A Thai Nguyen Hospital in 2024. Results: The highest rate of Escherichia coli resistance to levofloxacin was 93.48%, followed by ampicillin (86.96%), and the lowest resistance was to ceftazidime/avibactam (4%). Conversely, Escherichia coli was sensitive to ceftazidime/avibactam at 96%, amikacin at 89.1%, meropenem at 86.96%, and other antibiotics ranged from 30-60%. Pseudomonas aeruginosa bacteria are highly resistant to antibiotics, with a 100% resistance rate to amikacin, aztreonam, cefepime, ceftazidime, ciprofloxacin, colistin, levofloxacin, and meropenem; an 80% resistance rate to imipenem and meropenem. Enterobacter cloacae bacteria are resistant to almost all antibiotics tested, resistant to ampicillin, aztreonam, cefepime, cefotaxime, ceftriaxone, cefuroxime, ciprofloxacin, gentamicin, levofloxacin, piperacillin/tazobactam; trimethoprim/sulfamethoxazole is 100%; the lowest resistance rate is 40% for amikacin. Conclusion: Our study results show that the rate of antibiotic resistance in some bacteria commonly causing urinary tract infection is very high, especially Pseudomonas aeruginosa, Enterobacter cloacae, and Escherichia coli. The rate of multidrug resistance is very high in Pseudomonas aeruginosa and Enterobacter cloacae. The results of this study indicate the need to implement infection control measures to limit antibiotic resistance, with particular attention to multidrug-resistant strains.